STUDY OF THE MOVEMENT OF ELECTROMAGNETIC WAVES IN INTEGRATED CIRCUITS - Houda Amri; Mourad Zaabat (My University, 2021)
The advent of the integrated circuit revolutionized the electronics industry and paved the way for devices such as mobile phones, computers, CD players, televisions, and many appliances found around the home. In addition, the spread of the chips helped to bring advanced electronic devices to all parts of the world. For this reason, we have studied the transmission or the movement of electromagnetic waves to determine some proprieties of the integrated circuit